Tourism-driven carbon emissions and the innovation response: A cross-country analysis of extended QUAD economies - Shikha Daga; Kiran Yadav; Bhavna Yadav; Daniele Bregoli; Marco Ciro Liscio; Paolo Sospiro (Sustainable Futures)
Carbon emissions can be reduced by addressing robust environmental degradation. The current study examines the nuanced relationship between tourism and carbon emissions in the presence of technological innovation as a moderating variable for the Extended QUAD countries for 21 years (2000 to 2020). Using panel quantile regression and pre-diagnostic tests for cross-sectional dependence, slope heterogeneity, it emerged that technological innovation alone is not able to mitigate tourism's effect on carbon emissions. Results of quantile regression highlight a positive impact of technological innovation and tourism combined with emissions. Moreover, the variables employed, such as GDP, trade openness, and renewable energy show a strong correlation with emissions, underlining the necessity for policies targeting these factors to effectively reduce carbon footprints. Further, a positive correlation between trade openness and carbon emissions aligns with the pollution haven hypothesis; however, Environmental Kuznets Curve based hypothesis has been rejected by the presence of a positive relationship across different quantiles. The findings aim to offer insights for policymakers to harmonize economic growth with environmental sustainability pertaining to the tourism sector. The present study contributes to literature by exploring the role of technological innovation as a moderator in the tourism-emission nexus, providing a deeper understanding of sustainable tourism practices.